The Effect of Ballhandling and Agility Training on Extracurricular Women's Basketball Dribble at Public Vocational High School 1 Kedawung - Pratomo, Arif; Pramono, Harry; Soenyoto, Tommy (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
This research is motivated by the achievements of students who take extracurricular basketball at Public Vocational High School 1 Kedawung female participants due to poor dribble skills. The purpose of this research is to analyze the difference between the dribble crossover method and the two ball dribble method to the basketball dribble results the difference in the effect of high and low agility on basketball dribble results. Interaction of methods and agility to basketball dribble results. The method used is an experiment with 2x2 factorial design. Research Samples 24 female participants were taken by random technique from a total of 44 female participants. The instrument of agility illonis agility test. The instrument measures dribble using the basketball dribble test. ANOVA data analysis techniques were significant ÃŽÂ± = 0.05. Data collection techniques use the illonis agility test to measure agility and the basketball dribble test to measure dribble. The result of the research is that there is a difference in the effect of the method of ball-handling crossover dribble and two ball dribble exercises on the average basketball dribble yield of 9.917 while the average two-ball dribble is 8.333. There are differences in the effect of high and low agility on basketball dribble results. The average results of the high agility group of 9.750 low agility group of 8.500. There was an interaction of ball handling, and agility exercises, dribble ball handling crossover exercises with high agility of 11.167 were greater than the ball-handling two-ball dribble method by an average of 8.333.